Bionomics of the acarophagous ladybird beetle Stethorus tridens fed Tetranychus evansi - Fiaboe, K.K.M.; Gondim, M.G.C.; Moraes, G.J. de; Ogol, C.K.; Knapp, M. (Wiley, 2007)
The bionomics of Stethorus tridens Gordon fed Tetranychus evansi Baker & Pritchard were studied in the laboratory. The number of prey consumed by S. tridens increased with increasing instar levels and the total mean number consumed during immature development was 184.1 ± 18.02 T. evansi nymphs per individual. For adult male and adult female, the daily consumption was 41.3 ± 0.80 and 67.8 ± 1.69 nymphs, respectively. Stethorus tridens successfully developed to adulthood between 20 and 30°C but failed at 10, 15 and 35°C. The lower thermal threshold for egg-to-adult development estimated via linear regression and the modified Logan model was 9.2 and 8.1°C, respectively. The optimum and maximum temperatures for egg-to-adult development were around 29–31 and 32.9°C, respectively. Egg to adult development time was 23.8 ± 0.24, 17.4 ± 0.22, 16.2 ± 0.22 and 12.1 ± 0.16 days at 20, 24, 27 and 30°C, respectively. At 27°C, the sex ratio, expressed as the proportion of females, was 0.54 and the mean preoviposition, oviposition and postoviposition periods were 10.3 ± 0.67, 31.2 ± 4.74 and 30.2 ± 5.24 days, respectively. The oviposition rate was 4.0 ± 0.16 eggsfemaleday with a female mean longevity of 71.6 ± 6.19 days and an intrinsic rate of natural increase of 0.104. The potential of S. tridens as a candidate natural enemy of T. evansi is discussed.